Dormancy breaking methods in okra seeds (Research, Society and Development, 2020)
Okra seeds have dormancy, which impairs germination uniformity. The objective was to evaluate methods of breaking seed dormancy with pruning of the main stem and thinning of okra fruits. The experiment was implemented in an experimental field, using five treatments: pruning the main stem of okra at 40 and 50 days after transplanting the seedlings; chopped fruits from the bottom and chopped fruits from the top of the main stem at 50 days after transplant and seeds without breaking dormancy. The seeds were extracted in the laboratory, where analyzes were made of: number of seeds per fruit; thousand seed mass; purity; degree of humidity; germination; first count; Electric conductivity; dry mass of seedlings; emergency; emergency speed index; average emergency time. Apex pruning at 50 days (T3) provided greater NS per fruit than pruning at 40 days. The MMS was higher for fruits harvested in the upper position (T5) than in the lower position of the plant (T4). For the physiological characteristic of the seed (TPG) there was no difference in relation to the days of pruning of the apex of the plant (T2 and T3), but the result was higher than when pruning of the apex was not done (T1). MSP was superior with apex pruning at 50 days (T3). For PE, IVE and TME, pruning of the apex of the main stem at 40 and 50 days (T2 and T3) had no influence, but it was superior to the control (T1).